Isolation and Antioxidant Activity of Flavonoid Compound in Ethanolic Extract of Celery Leaves (Apium graveolens L.) - Alifa Husnun Kholieqoh; Khairul Anam; Dewi Kusrini (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Celery (Apium graveolens L.) is a plant that belongs to the Apiaceae family and is widely used as a medical plant for low blood pressure, heart tonic, and to prevent cardiovascular disease. This study aims to obtain flavonoid compounds, identify, and test the antioxidant activity of flavonoid compounds and crude extracts from celery leaves. The research procedures consisted of four steps, the first of which was a preliminary test. The second step involved isolating and separating flavonoid components by vacuum liquid chromatography, gravitational column chromatography, and preparative thin layer chromatography. The third step was to identify flavonoid compounds using reagent shift, FTIR, and LCMS/MS. And finally, antioxidant activity was evaluated using the DPPH method. The preliminary test result showed that the ethanolic extract of leaves and stems had a total flavonoid content of 13.99 and 2.46 mg QE/g of dry weight. Both dry leaves and crude extract of celery leaves contained alkaloids, saponin, flavonoid, tannin, quinone, and steroid/triterpenoid, as determined by phytochemical screening. Isolation and separation of flavonoids yielded A2.I and A2.II isolates, with respective weights of 8 mg and 14 mg. Identification of flavonoid compounds using reagent shift showed that two isolates have the basic structure of the flavone group. A2.I isolate had OH groups at 4’, 5, and 7, while A2.II isolate had OH groups at 3’, 4’, 5, and 7. The FTIR analysis revealed that both compounds contain functional groups, including O-H, C=O, C=C aromatic, C-O ether, C-O alcohol, and C-H aromatic ring. According to LCMS/MS analysis, the molecular weights of A2.I and A2.II were 270 g/mol and 286 g/mol, respectively. All of the identification methods for isolates showed that A2.I was apigenin and A2.II was luteolin. Antioxidant activity by DPPH method for a viscous extract of celery leaves, A2.I, and A2.II were 775.41, 288.95, and 184.35 µg/mL, respectively.